The fatiguing effects of camera use in virtual meetings: A within-person field experiment. - Shockley, Kristen M.; Gabriel, Allison S.; Robertson, Daron; Rosen, Christopher C.; Chawla, Nitya; Ganster, Mahira L.; Ezerins, Maira E. (Journal of Applied Psychology, 2021)
The COVID-19 pandemic propelled many employees into remote work arrangements, and face-to-face meetings were quickly replaced with virtual meetings. This rapid uptick in the use of virtual meetings led to much popular press discussion of virtual meeting fatigue (i.e., "Zoom fatigue"), described as a feeling of being drained and lacking energy following a day of virtual meetings. In this study, we aimed to better understand how one salient feature of virtual meetings-the camera-impacts fatigue, which may affect outcomes during meetings (e.g., participant voice and engagement). We did so through the use of a 4-week within-person experience sampling field experiment where camera use was manipulated. Drawing from theory related to self-presentation, we propose and test a model where study condition (camera on versus off) was linked to daily feelings of fatigue; daily fatigue, in turn, was presumed to relate negatively to voice and engagement during virtual meetings. We further predict that gender and organizational tenure will moderate this relationship such that using a camera during virtual meetings will be more fatiguing for women and newer members of the organization. Results of 1,408 daily observations from 103 employees supported our proposed model, with supplemental analyses suggesting that fatigue affects same-day and next-day meeting performance. Given the anticipated prevalence of remote work even after the pandemic subsides, our study offers key insights for ongoing organizational best practices surrounding virtual meetings. (PsycInfo Database Record (c) 2021 APA, all rights reserved).